2001
DOI: 10.2337/diabetes.50.4.776
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon-Like Peptide 1 Increases Secretory Burst Mass of Pulsatile Insulin Secretion in Patients With Type 2 Diabetes and Impaired Glucose Tolerance

Abstract: The insulinotropic gut hormone glucagon-like peptide (GLP)-1 increases secretory burst mass and the amplitude of pulsatile insulin secretion in healthy volunteers without affecting burst frequency. Effects of GLP-1 on secretory mechanisms in type 2 diabetic patients and subjects with impaired glucose tolerance (IGT) known to have impaired pulsatile release of insulin have not yet been studied. Eight type 2 diabetic patients (64 ؎ 9 years, BMI 28.9 ؎ 7.2 kg/m 2 , HbA 1c 7.7 ؎ 1.3%) and eight subjects with IGT (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
3

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 48 publications
(66 reference statements)
2
32
0
3
Order By: Relevance
“…An improved regularity of release pattern was not expected in this study of healthy subjects. In Type II diabetes GLP-1 has, in a preliminary report, also been shown to increase insulin secretion by amplification of the burst mass with no effect on the burst frequency when GLP-1 was given as an overnight infusion [25]. This is similar to the findings in our study.…”
Section: Discussionsupporting
confidence: 91%
“…An improved regularity of release pattern was not expected in this study of healthy subjects. In Type II diabetes GLP-1 has, in a preliminary report, also been shown to increase insulin secretion by amplification of the burst mass with no effect on the burst frequency when GLP-1 was given as an overnight infusion [25]. This is similar to the findings in our study.…”
Section: Discussionsupporting
confidence: 91%
“…It is therefore likely that the phase relationship between cAMP and Ca 2+ signals varies depending on the relative expression levels of different adenylyl cyclases and phosphodiesterases as well as on the type of stimulus (Fridlyand et al, 2007). The coordinated elevations and mutual enhancement of Ca 2+ and cAMP signals observed in GLP-1-stimulated cells should be an exquisite trigger for exocytosis and may explain how the incretin hormone selectively enhances the pulsatile component of insulin release in healthy and diabetic subjects (Pørksen et al, 1998;Ritzel et al, 2001).…”
Section: Cyclic Ampmentioning
confidence: 99%
“…Measurements in the portal vein of dogs and humans have indicated that virtually all insulin (>70-75%) is released in a pulsatile fashion (Pørksen et al, 1995;Pørksen et al, 1997). Early estimates of pulse intervals are somewhat variable due to technical limitations but later data indicate a periodicity of 4-6 min in humans (Storch et al, 1993;Pørksen et al, 1997;Ritzel et al, 2001) and dogs (Pørksen et al, 1996). The insulin-releasing β-cells are located in about 1 million islets of Langerhans distributed within the 25 cm long human pancreas.…”
mentioning
confidence: 99%
“…Insulin secretion occurs in a pulsatile manner, and GLP-1 increases the amplitude of each pulse without changing the pulse frequency [24,25,95]. …”
Section: E the Insulin Secretagogue Action Of Glp-1mentioning
confidence: 99%